2016
DOI: 10.1371/journal.pone.0152975
|View full text |Cite
|
Sign up to set email alerts
|

HEK293T Cells Are Heterozygous for CCR5 Delta 32 Mutation

Abstract: C-C chemokine receptor 5 (CCR5) is a receptor for chemokines and a co-receptor for HIV-1 entry into the target CD4+ cells. CCR5 delta 32 deletion is a loss-of-function mutation, resistant to HIV-1 infection. We tried to induce the CCR5 delta 32 mutation harnessing the genome editing technique, CRISPR-Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats, CRISPR and CRISPR associated protein 9, Cas9) in the commonly used cell line human embryonic kidney HEK 293T cells. Surprisingly, we found that HEK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…2D). Surprisingly, the sequencing results also demonstrated all the clones had natural 32-bp deletion on the other allele, which is consistent with the recent report that HEK293T cells are heterozygous for CCR5 D32 mutation [21].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2D). Surprisingly, the sequencing results also demonstrated all the clones had natural 32-bp deletion on the other allele, which is consistent with the recent report that HEK293T cells are heterozygous for CCR5 D32 mutation [21].…”
Section: Resultssupporting
confidence: 91%
“…Surprisingly, we detected no biallelic integration at first and further sequencing results showed all the clones had the 32‐bp deletion on the other allele. This accidental discovery is just confirmed by the later report that HEK293T cells are heterozygous for CCR5 Δ32 mutation . As the CCR5 .sgRNA target site was chosen from the missing sequence, CCR5 .sgRNA‐Cas9 failed to target the allele with the Δ32 mutation to mediate the integration.…”
Section: Discussionmentioning
confidence: 90%
“…3a, b, d, e ), though we detected a lower number of L1-ORFeus insertions compared to MYC and RAG1 loci, likely due to the lower efficiency of the CCR5 CRISPR/Cas9 (Supplementary Fig. 3c ) as well as only one copy of the CCR5 gene can be edited since HEK293T cells are heterozygous for CCR5 delta 32 mutation 57 . Again, retrotransposition of the spliced L1-ORFeus transcript were observed at CCR5 CRIPSR/Cas9 editing site only in L1-ORFeus, but not in L1-RTm (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Unexpectedly, three fragments were observed in the sorted blasts and LSC from TARP-high pedAML patients and the MV4; 11 cell line. Cloning and sequencing of each fragment (Online Supplementary Figure S5B) revealed that the largest fragments were artificial heteroduplexes, 44 whereas the smallest fragments were identical to the fragments from Kg-1a and LNCaP. Medium-sized fragments were consistently 48 bp longer, and showed the same size as the HSB-2 amplicon, a T-cell acute lymphoblastic leukemia (T-ALL) cell line with functional TRGC2 rearrangements.…”
Section: A B Cmentioning
confidence: 99%